Non-Sleep Non-Apnea Nasal Fiber Optic Intubation for Difficult Airway Management: A Case Series - Bora, Fivilia Anjelina; I Made Gede Widnyana (Journal of Anesthesiology and Clinical Research, 2023)
Introduction: Patients with tumors on the neck and mouth are known to be at risk for difficult intubation. Failing to secure the airway can lead to increased patient morbidity and mortality. This study aimed to present a case series with non-sleep non-apnea fiber optic intubation for difficult airway management. Case presentation: In this paper, we present three patients; a 57-year-old woman, a 59-year-old man, and a 68-year-old woman who have airway problems with a tumor located on their neck and mouth but were successfully intubated by non-sleep non-apnea nasal fiber optic intubation, one of airway management technique. Good visualization was achieved by fiber optic devices. Preparing the patient holistically and systematically during the perioperative period was the other important thing to do. MOANS score and LEMON score are used to predict the potential event of a difficult airway preoperatively. These scores help the physician to decide what step will be done with the patient. Conclusion: Anesthetic morbidity and mortality can be reduced with better preoperative evaluation and clear guidelines and practice for difficult intubation.